2016
DOI: 10.1093/ehjcvp/pvw041
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drug use is associated with increased risk of out-of-hospital cardiac arrest: a nationwide case–time–control study

Abstract: Use of non-selective NSAIDs was associated with an increased early risk of OHCA. The result was driven by an increased risk of OHCA in ibuprofen and diclofenac users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 29 publications
0
53
0
6
Order By: Relevance
“…Celecoxib, a COX-2 inhibitor, has been associated with fewer CVD events compared to ibuprofen and naproxen in the PRECISION trial; however, this result was not significant [186]. Additionally, a recent study using a nationwide cohort of 28,947 patients with OHCA of whom 3376 patients were treated with an NSAID also found a significantly increased risk of OHCA among patients who used ibuprofen and diclofenac but not those who consumed naproxen, celecoxib, or rofecoxib [187]. Another lipid mediator is anti-leukotrienes, as arachidonic acid metabolism by arachidonate 5-lipoxygenase (5-LO) and 5-LO-activating protein (FLAP) generates leukotrienes that have atherosclerotic implications, including lesion development, induction and activation of leukocytes, SMC proliferation, and endothelial dysfunction [226].…”
Section: Efficacies Of Existing Anti-inflammatory Therapeutics In mentioning
confidence: 99%
“…Celecoxib, a COX-2 inhibitor, has been associated with fewer CVD events compared to ibuprofen and naproxen in the PRECISION trial; however, this result was not significant [186]. Additionally, a recent study using a nationwide cohort of 28,947 patients with OHCA of whom 3376 patients were treated with an NSAID also found a significantly increased risk of OHCA among patients who used ibuprofen and diclofenac but not those who consumed naproxen, celecoxib, or rofecoxib [187]. Another lipid mediator is anti-leukotrienes, as arachidonic acid metabolism by arachidonate 5-lipoxygenase (5-LO) and 5-LO-activating protein (FLAP) generates leukotrienes that have atherosclerotic implications, including lesion development, induction and activation of leukocytes, SMC proliferation, and endothelial dysfunction [226].…”
Section: Efficacies Of Existing Anti-inflammatory Therapeutics In mentioning
confidence: 99%
“…Harmful knee OA treatments like NSAIDs (causing cardiovascular disease10 and stomach ulcers), opiates (leading to high rates of addiction) and arthroscopic surgery (risks without any net benefit) continue to be funded in the Netherlands, as in most countries. Like many other countries, supervised exercise therapy (efficacious without serious side effects) is poorly funded.…”
Section: Reimbursement For Knee Oa Procedures In the Netherlandsmentioning
confidence: 99%
“…The authors of the study, which was reported in the European Heart Journal: Cardiovascular Pharmacotherapy, 1 said that the findings were a stark reminder that NSAIDs were not harmless and should only be used after consulting a healthcare professional.…”
mentioning
confidence: 99%